Bear wants more - Wilson, Karma; Chapman, Jane 1970- (New York Margaret K. McElderry Books, 2003)
When spring comes, Bear wakes up very hungry and is treated to great food by his friends.
Keywords: Bears -- Fiction; Food -- Fiction; Animals -- Fiction; Stories in rhyme